2016
DOI: 10.1007/s10916-016-0571-9
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Demand Forecasting in a Tertiary Pediatric Intensive Care Unit

Abstract: Forecasts of the demand for medical supplies both directly and indirectly affect the operating costs and the quality of the care provided by health care institutions. Specifically, overestimating demand induces an inventory surplus, whereas underestimating demand possibly compromises patient safety. Uncertainty in forecasting the consumption of medical supplies generates intermittent demand events. The intermittent demand patterns for medical supplies are generally classified as lumpy, erratic, smooth, and slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Figure 1 shows the breakdown of COVID-19 vaccination by those who have been partially or completely vac-cinated in Africa. Some believe that machine learning and block chain technology can help with this task [1][2][3][4] . One of the key factors for effective supply chain management is the forecasting of health products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the breakdown of COVID-19 vaccination by those who have been partially or completely vac-cinated in Africa. Some believe that machine learning and block chain technology can help with this task [1][2][3][4] . One of the key factors for effective supply chain management is the forecasting of health products.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has caused significant and unprecedented pressure in most of the products' supply chains worldwide. Previous research work related to the forecasting of vaccine supply chain disruption identified some factors that lead to it [1][2][3][4][5][6] . The early prediction of excess demand of vaccine during epidemics will have significant implications for supply chain managers and government officials.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] However, the application of demand forecasting methods remains relatively underdeveloped in healthcare when compared to other sectors. [20][21][22] Methods involving linear regression are commonly used as they provide reasonably accurate results, are easy to interpret and have wide applications in modeling. [23][24][25] Furthermore, the management of medical supplies has been a priority due to uncertainties in demand and risk of shortages that affect patient safety.…”
Section: Introductionmentioning
confidence: 99%